Essential oil of Lippia alba and its main constituent citral block the excitability of rat sciatic nerves - Sousa,D.G. (2015)
Lippia alba is empirically used for infusions, teas, macerates, and hydroalcoholic extracts because of its antispasmodic, analgesic, sedative, and anxiolytic effects. Citral is a mixture of trans-geranial and cis-neral and is the main constituent of L. alba essential oil and possesses analgesic, anxiolytic, anticonvulsant, and sedative effects. The present study evaluated the effects of the essential oil of L. alba (EOLa) and citral on compound action potentials (CAPs) in Wistar rat sciatic nerves. Both drugs inhibited CAP in a concentration-dependent manner. The calculated half-maximal inhibitory concentrations (IC50) of peak-to-peak amplitude were 53.2 µg/mL and 35.00 µg/mL (or 230 µM) for EOLa and citral, respectively. Peak-to-peak amplitude of the CAP was significantly reduced by 30 µg/mL EOLa and 10 µg/mL citral. EOLa and citral (at 60 and 30 µg/mL, values close to their respective IC50 for CAP blockade) significantly increased chronaxy and rheobase. The conduction velocity of the first and second CAP components was statistically reduced to ∼86% of control with 10 µg/mL EOLa and ∼90% of control with 3 µg/mL citral. This study showed that EOLa inhibited nerve excitability and this effect can be explained by the presence of citral in its composition. Both EOLa and citral showed inhibitory actions at lower concentrations compared with other essential oils and constituents with local anesthetic activity. In conclusion, these data demonstrate that EOLa and citral are promising agents in the development of new drugs with local anesthetic activity.